Effect of thermal history on the ionic conductivity of block copolymer electrolytes. Issue 12 (9th April 2013) - Mullin, Scott A.; Teran, Alexander A.; Yuan, Rodger; Balsara, Nitash P.
ABSTRACT We have studied the effect of thermal history on ionic conductivity of block copolymer electrolytes. Previous work on block copolymer electrolytes composed of polystyrene‐b‐poly(ethylene oxide) (SEO) and lithium bis(trifluoromethanesulfone) imide (LiTFSI) salt was restricted to lamellar morphologies. This study addresses both cylindrical and lamellar morphologies. The conductivity of low molecular weight samples decreases after they are annealed. In contrast, the conductivity of high molecular weight samples is generally unaffected by annealing. These results are explained in the context of connectivity and composition of the conducting phase. © 2013 Wiley Periodicals, Inc. J. Polym. Sci. Part B: Polym. Phys. 2013, 51, 927–934